Effect of residence time on the torrefaction characteristics of Calliandra wood as solid biofuel - Amrul, Amrul; Apriyanto, Agus; Prayitno, Hadi; Azmar, Muhammad Sajid (Politeknik Negeri Lhokseumawe, 2025)
Increasing energy demand and the environmental impact of fossil fuel use have prompted the search for alternative and more sustainable energy sources. Calliandra wood (Calliandra Calothyrsus) as a renewable solid fuel has relatively high heating value and rapid growth. This study aims to examine the effect of residence time variation in the torrefaction process on the characteristics of Calliandra wood chips This research was conducted experimentally using a tubular-type continuous torrefaction reactor at two temperatures, namely 275 and 300°C, with three residence time variations: 10, 20, and 30 minutes. The main parameters analyzed included calorific value, proximate and ultimate composition, mass yield, and energy yield. The results showed that the longer the residence time, the heating value and carbon content continued to increase, but there was a decrease in mass and energy yield. At 300°C with a residence time of 30 minutes, the highest heating value was obtained at 6,399 kcal/kg, but the mass yield remained at 35%. In contrast, at 275°C with a residence time of 10 minutes, the heating value increased to 4,632 kcal/kg with a mass yield of 83%. Optimal conditions were obtained at 275°C with a residence time of 20 minutes, resulting in a heating value of 5,387 kcal/kg with a mass yield of 70%, which balanced the energy efficiency and the amount of biomass retained. Although the torrefaction process was shown to improve the quality of biomass as a solid fuel and the longer residence time resulted in higher energy, there was a trade-off in the form of reduced biomass mass. Torrefaction also makes the biomass more hydrophobic and resistant to biological damage. The results of this study are expected to be a reference for the development of torrefaction technology to support the utilization of renewable energy in Indonesia.